Disruption of the imprinted Grb10 gene leads to disproportionate overgrowth by an Igf2-independent mechanism - Charalambous, Marika (National Academy of Sciences, 2003)
To investigate the function of the Grb10 adapter protein, we have generated mice in which the Grb10 gene was disrupted by a gene-trap insertion. Our experiments confirm that Grb10 is subject to genomic imprinting with the majority of Grb10 expression arising from the maternally inherited allele. Consistent with this, disruption of the maternal allele results in overgrowth of both the embryo and placenta such that mutant mice are at birth ≈30% larger than normal. This observation establishes that Grb10 is a potent growth inhibitor. In humans, GRB10 is located at chromosome 7p11.2–p12 and has been associated with Silver–Russell syndrome, in which ≈10% of those affected inherit both copies of chromosome 7 from their mother. Our results indicate that changes in GRB10 dosage could, in at least some cases, account for the severe growth retardation that is characteristic of Silver–Russell syndrome. Because Grb10 is a signaling protein capable of interacting with tyrosine kinase receptors, we tested genetically whether Grb10 might act downstream of insulin-like growth factor 2, a paternally expressed growth-promoting gene. The result indicates that Grb10 action is essentially independent of insulin-like growth factor 2, providing evidence that imprinting acts on at least two major fetal growth axes in a manner consistent with parent–offspring conflict theory.